Korean honorifics in flux - Ryu, Hyeonsook (Acta linguistica asiatica, 2023)
This paper aims to demonstrate the close connection between society and politeness styles by analyzing Korean language textbooks for foreign learners published by Seoul National University Language Education Institute from 2000 to 2019. Changes in these textbooks indicate a dynamic interplay between society and language. The study reveals notable shifts in politeness styles, particularly the near-complete replacement of the formal hasipsioche with the polite informal style haeyoche. This paper seeks to connect the observed changes in textbooks and shifts in Korean culture and society. The paper offers a brief introduction to Korean history, society, and culture, highlighting their relevance to the Korean language in general and specifically to Korean in a second language education.
Keywords: Korean honorifics; Korean language; Korean society; korejska družba; korejske spoštljive oblike; korejski jezik; secondlanguage textbooks; sociolinguistics; sociolingvistika; učbeniki tujih jezikov